Fractional dose of intradermal compared to intramuscular and subcutaneous vaccination - A systematic review and meta-analysis (2020)
Background Vaccine supply shortages are of global concern. We hypothesise that intradermal (ID) immunisation as an alternative to standard routes might augment vaccine supply utilisation without loss of vaccine immunogenicity and efficacy. Methods We conducted a systematic review and meta-analysis searching Medline, Embase and Web of Science databases. Studies were included if: licensed, currently available vaccines were used; fractional dose of ID was compared to IM or SC immunisation; primary immunisation schedules were evaluated; immunogenicity, safety data and/or cost were reported. We calculated risk differences (RD). Studies were included in meta-analysis if: a pre-defined immune correlate of protection was assessed; WHO-recommend schedules and antigen doses were used in the control group; the same schedule was applied to both ID and control groups (PROSPERO registration no. CRD42020151725). Results The primary search yielded 5,873 articles, of which 156 articles were included; covering 12 vaccines. Non-inferiority of immunogenicity with 20-60% of antigen used with ID vaccines was demonstrated for influenza (H1N1: RD -0·01; 95% CI -0·02, 0·01; I 2 = 55%, H2N3: RD 0·00; 95% CI -0·01, 0·01; I2 = 0%, B: RD -0·00; 95% CI -0·02, 0·01; I2 = 72%), rabies (RD 0·00; 95% CI -0·02, 0·02; I2 = 0%), and hepatitis B vaccines (RD -0·01; 95% CI -0·04, 0·02; I2 = 20%). Clinical trials on the remaining vaccines yielded promising results, but are scarce. Conclusions There is potential for inoculum/antigen dose-reduction by using ID immunisation as compared to standard routes of administration for some vaccines (e.g. influenza, rabies). When suitable, vaccine trials should include an ID arm.